Discovery of the first unconventional myosin: Acanthamoeba myosin-I - Pollard, Thomas D.; Korn, Edward D. (Frontiers in Physiology, 2023)
Having characterized actin from Acanthamoeba castellanii (Weihing and Korn 1971) and knowing that myosin had been isolated from the slime mold Physarum (Hatano and Tazawa 1968, Adelman and Taylor 1969), we set out in 1969 to find myosin in Acanthamoeba. We used K-EDTA-ATPase activity to assay myosin, because it is a unique feature of muscle myosins. After slightly less than three years, we purified a K-EDTA ATPase that interacted with actin. Actin filaments stimulated the Mg-ATPase activity of the crude enzyme, but this was lost with further purification. Recombining fractions from the column where this activity was lost revealed a "cofactor" that allowed actin filaments to stimulate the Mg-ATPase of the purified enzyme. The small size of the heavy chain and physical properties of the purified myosin were unprecedented, so many were skeptical, assuming that our myosin was a proteolytic fragment of a larger myosin similar to muscle or Physarum myosin. Subsequently our laboratories confirmed that Acanthamoeba myosin-I is a novel unconventional myosin that interacts with membrane lipids (Adams and Pollard 1989) and that the cofactor is a myosin heavy chain kinase (Maruta and Korn 1977). Phylogenetic analysis (Odronitz and Kollmar 2007) later established that class I myosin was the first myosin to appear during the evolution of eukaryotes.